Views of patients with advanced disease and their relatives on participation in palliative care research - Vlckova, Karolina; Polakova, Kristyna; Tuckova, Anna; Houska, Adam; Loucka, Martin (BMC palliative care, 2021)
BACKGROUND: Patients with advanced disease may not be invited to participate in research based on the assumption that participation would be too burdensome for them. The aim of this study was to explore how patients with advanced disease and their relatives evaluate their experience with research participation. METHOD: This study used data from two parts of a larger project. The first dataset was a cross-sectional questionnaire study focused on priorities at the end of life. The second dataset used a longitudinal design with structured interviews on prognostic awareness. In both studies, participants evaluated their experience on a 5-point Likert scale and specified their motivation in an open-ended question. Data were collected in 6 hospitals in the Czech Republic with patients with advanced disease and life expectancy less than 1 year and their relatives. Data were analysed using non-parametric tests and thematic analysis. RESULTS: First dataset consisted of 167 patients and 102 relatives, and second dataset consisted of 135 patients and 92 relatives (in total, 496 respondents). Results were similar in both datasets, with half of the sample (53%, 48%) scoring neutral, and over 30% of the sample identified their experience as interesting. The most significant factors associated with the evaluation were religiosity (p = 0.001) and the type of diagnosis (p = 0.04). Motivation for participation was to improve care, support research, express own opinion, opportunity to talk and trusting relationship. CONCLUSIONS: Patients with advanced disease and relatives do not mind participating in palliative care research, and it can be even a positive experience for them.
Keywords: paliativní péče; průzkumy a dotazníky; Cross-Sectional Studies; Hospice and Palliative Care Nursing; Surveys and Questionnaires; Qualitative Research; rodina; Humans; lidé; průřezové studie; Palliative Care; Family; kvalitativní výzkum; hospicová a paliativní ošetřovatelská péče